1996
DOI: 10.1073/pnas.93.15.7985
|View full text |Cite
|
Sign up to set email alerts
|

Peptide methionine sulfoxide reductase contributes to the maintenance of adhesins in three major pathogens.

Abstract: Pathogenic bacteria rely on adhesins to bind to host tissues. Therefore, the maintenance of the functional properties of these extracellular macromolecules is essential for the pathogenicity of these microorganisms. We report that peptide methionine sulfoxide reductase (MsrA), a repair enzyme, contributes to the maintenance of adhesins in Streptococcus pneumoniae, Neisseria gonorrhoeae, and Escherichia coli. A screen of a library of pneumococcal mutants for loss of adherence uncovered a MsrA mutant with 75% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
147
1
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(156 citation statements)
references
References 64 publications
5
147
1
3
Order By: Relevance
“…Msr enzymes have also been shown to be necessary for host colonization and persistence in Lactobacillus reuteri and H. pylori (Alamuri & Maier, 2004;Walter et al, 2005), which is not only due to protection against oxidative stress but also through a possible role in the maintenance and expression of adhesins, allowing persistence and biofilm formation (Wizemann et al, 1996). Host colonization and persistence studies of the three mutant strains studied here would also shed further light on the in vivo role of MsrA and MsrB from C. jejuni.…”
Section: Discussionmentioning
confidence: 99%
“…Msr enzymes have also been shown to be necessary for host colonization and persistence in Lactobacillus reuteri and H. pylori (Alamuri & Maier, 2004;Walter et al, 2005), which is not only due to protection against oxidative stress but also through a possible role in the maintenance and expression of adhesins, allowing persistence and biofilm formation (Wizemann et al, 1996). Host colonization and persistence studies of the three mutant strains studied here would also shed further light on the in vivo role of MsrA and MsrB from C. jejuni.…”
Section: Discussionmentioning
confidence: 99%
“…Both MsrA and MsrB have been shown to play a role in the oxidative stress response and pathogenicity of microorganisms. For example, a decrease in infectivity of Streptococcus pneumoniae has been observed after the deletion of the msrAB1 gene (33). Similarly, a study on the pathogenic actinomycete Mycobacterium tuberculosis, which can survive major reactive oxygen species and reactive nitrogen species attacks during the host immune response within macrophages, has shown that MsrA and MsrB single and double deletion strains were sensitive for oxidative stress (34).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the CBPs bound to receptors on the human cells and thereby prevented CBP-mediated bacterial attachment. The demonstration of a direct CBPhuman cell interaction that leads to a loss of adherence distinguishes the CBPs from other pneumococcal proteins, such as the peptide permeases, PlpA (Cundell et al, 1995a), AmiA (Cundell et al, 1995a), a pyruvate oxidase (SpxB) (Spellerberg et al, 1996) and the peptide methionine sulphoxide reductase (MsrA) (Wizemann et al, 1996), which have been identified in genetic studies as affecting bacterial adherence. Although loss of these elements decreases the capacity of the bacteria to adhere, there was no direct evidence that they exhibited competitive inhibition of adherence, a key characteristic of a structural adhesin.…”
Section: Discussionmentioning
confidence: 99%